In-situ observation of grain growth and phase transformation in weld zone of Ti-6Al-4V titanium alloy by laser welding with filler wire. (10th May 2021) - Fang, Naiwen; Guo, Erjun; Xu, Kai; Huang, Ruisheng; Ma, Yiming; Chen, Yongsheng; Yang, Yicheng; Xie, Jilin
Abstract: Through in situ observation at high temperature confocal laser scanning microscope, the microstructures and phase transformation of Ti-6Al-4V titanium alloy welded joint by laser welding with filler wire during heating, heat preservation and cooling process in simulating welding thermal cycle were studied. When the weld microstructure was heated to 380 °C, obvious grain growth was observed. After heating to 1 050 °C, weld microstructures were mostly composed of coarse β -columnar grains. During the heat preservation process of the weld metal, it could be found that the β phase boundary moved slowly. In the cooling process of weld microstructures, with the increase of the cooling rate, the transition temperature for new phase precipitation decreased gradually, and that for ending the precipitation increased gradually. The microstructures after cooling to room temperature at a rate of 0.5 °C/s and 5 °C s −1 were composed of α phases. At 20 °C s −1, acicular α ′ martensite appeared in the microstructures. At 80 °C s −1, precipitated phases were all composed of acicular α ′ martensite.The Ti-6Al-4V titanium alloy weld microstructure by laser welding with filler wire is completely hexagonal close packed (HCP) crystal structure.The hardness of the weld microstructures was improved with the cooling rate getting faster.